THE BACTERIOCIN ANTIMICROBIAL TEST ACTIVITY OF PROBIOTIC BACTERIA ISOLATED FROM GIANT PRAWNS (Macrobrachium rosenbergii) - Popy Wardani; Feliatra '; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted to test the antimicrobial activity of bacteriocin isolates of probiotic bacteria isolated from giant prawns (Macrobrachium rosenbergii). The method used was experiment method with tested the inhibition against pathogenic bacteria (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas stutzeri). The results showed that bacteriocin capable of inhibiting the growth of pathogenic bacteria of P. stutzeri, A. hydrophila and V. alginolyticus. The best isolates obtained from results of this research was UG4 with clear zones ranging from 7.2 to 11.4 mm and the inhibition activity of 1476.53 mm²/mL after fragmentation with (NH4)2SO4 against pathogenic bacteria P. stutzeri was incubated at room temperature (37°C). This inhibition was caused by the presence of antimicrobial compounds that are produced by probiotic bacteria, namely bacteriocin. For isolates UG2 codes, the bacteria was resistant in which characterized by the formation of bluring zone around the paper disc.Key words: Antimicrobial activity, probiotics, bacteriocins, giant prawns